1995
DOI: 10.1089/neu.1995.12.897
|View full text |Cite
|
Sign up to set email alerts
|

Posttraumatic Cerebral Arterial Spasm

Abstract: Posttraumatic cerebral arterial spasm (vasospasm) has been demonstrated in the past by angiography, and recently by transcranial Doppler ultrasonography. Posttraumatic vasospasm is a delayed complication that involves the large basal intracranial arteries (e.g., internal carotid, middle cerebral, basilar) and occurs in 25-40% of head trauma patient. The time course of posttraumatic vasospasm resembles that of vasospasm associated with aneurysmal subarachnoid hemorrhage with onset occurring 2 or more days after… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
39
1
2

Year Published

1997
1997
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(43 citation statements)
references
References 21 publications
1
39
1
2
Order By: Relevance
“…While previous studies characterized the formation of vasospasm following trauma, 19,20,22,23,29,31,32,36,37 few were able to correlate delayed ischemic deficits and outcomes with its presence, 15,31,32,37 and even fewer described the safety or efficacy of endovascular interventions in this setting. 12 In addition, while not specifically correlated with vasospasm occurrence, there was a considerable predominance of blast-induced head injury in our population.…”
mentioning
confidence: 99%
“…While previous studies characterized the formation of vasospasm following trauma, 19,20,22,23,29,31,32,36,37 few were able to correlate delayed ischemic deficits and outcomes with its presence, 15,31,32,37 and even fewer described the safety or efficacy of endovascular interventions in this setting. 12 In addition, while not specifically correlated with vasospasm occurrence, there was a considerable predominance of blast-induced head injury in our population.…”
mentioning
confidence: 99%
“…For example, Hadani et al [8] found the incidence of PTV in the anterior or posterior circulation increased from 43% to 58% if traumatic subarachnoid hemorrhage (tSAH) was present. Romner et al [15] found anterior circulation PTV incidence increased from 28% to 41% with tSAH, a correlation that has been further supported by other authors as well [12,24,31,32]. Some studies, however, have correlated PTV with subdural or epidural hematoma [12,13,24,42], and found no relationship with presence of tSAH [13,42].…”
Section: Posttraumatic Cerebral Artery Vasospasmmentioning
confidence: 78%
“…PTV typically develops between 12 h and 5 days after injury and lasts anywhere between 12 h and 30 days [7, 10-13, 15, 16, 19-21]. Although PTV is an independent predictor of permanent neurological deficit and poor outcome in many studies [3,4,6,7,10,[22][23][24][25], it continues to be an under-recognized source of secondary injury following TBI and guidelines for screening and treatment of PTV do not currently exist [26].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[24,33,50] This discrepancy may result, in part, from other factors not reflected in either ICP or CPP, such as disturbed autoregulation, [2,14,34] traumatic vasospasm, [29] or neurochemical changes such as elevated excitatory amino acids, [1] which may adversely influence cerebral blood flow (CBF) or tissue oxygenation and contribute to infarction.…”
mentioning
confidence: 99%